Вы находитесь на странице: 1из 7

# Illustrating

the
Antiderivative
of a Function
Match the functions in Column A with their
RECALL corresponding derivatives in Column B.
COLUMN A COLUMN B
G 1. 𝑭 𝒙 = 𝒙𝟑 + 𝟐𝒙𝟐 + 𝒙 A. 𝒇 𝒙 = 𝟒𝒙𝟑 + 𝟑𝒙𝟐
C 2. 𝑭 𝒙 = 𝒙𝟑 + 𝒙𝟐 + 𝒙 B. 𝒇 𝒙 = 𝟗𝒙𝟐 − 𝟑
H 3. 𝑭 𝒙 = 𝒙𝟒 + 𝟑𝒙𝟑 + 𝟏 C. 𝒇 𝒙 = 𝟑𝒙𝟐 + 𝟐𝒙 + 𝟏
A 4. 𝑭 𝒙 = 𝒙𝟒 + 𝒙𝟑 + 𝟐 D. 𝒇 𝒙 = 𝟗𝒙𝟐 + 𝟔𝒙
E 5. 𝑭 𝒙 = 𝒙𝟐 + 𝟐𝒙 + 𝟏 E. 𝒇 𝒙 = 𝟐𝒙 + 𝟐
F 6. 𝑭 𝒙 = 𝒙𝟐 − 𝟐𝒙 + 𝟏 F. 𝒇 𝒙 = 𝟐𝒙 − 𝟐
D 7. 𝑭 𝒙 = 𝟑𝒙𝟑 + 𝟑𝒙𝟐 + 𝟏 G. 𝒇 𝒙 = 𝟑𝒙𝟐 + 𝟒𝒙 + 𝟏
B 8. 𝑭 𝒙 = 𝟑𝒙𝟑 − 𝟑𝒙 + 𝟏 H. 𝒇 𝒙 = 𝟒𝒙𝟑 + 𝟗𝒙𝟐
DEFINE Terminologies and Notations
 Antidifferentiation is the process of finding the antiderivative.
 A function 𝑭 is called an antiderivative of 𝒇 on an interval 𝑰 if 𝑭′ (𝒙) = 𝒇(𝒙).
 The symbol ʃ , also called the integral sign, denotes the operation of
antidifferentiation.
 The function 𝒇 is called the integrand.
 If 𝐹 is an antiderivative of 𝒇, we write ‫ 𝒙 𝑭 = 𝒙𝒅 𝒙 𝒇 ׬‬+ 𝑪, where 𝑪 is called the
constant of integration and 𝒅𝒙 is called the variable of integration.
 The expression 𝑭 𝒙 + 𝑪 is called the general antiderivative of 𝒇. Meanwhile, each
antiderivative of 𝒇 is called a particular antiderivative of 𝒇.
Find the antiderivative of the following
EXAMPLES
functions. (GOING BACK TO THE DRILL)

1. 𝒇 𝒙 = 𝟒𝒙𝟑 + 𝟑𝒙𝟐 5. 𝒇 𝒙 = 𝟐𝒙 + 𝟐
2. 𝒇 𝒙 = 𝟗𝒙𝟐 + 𝟑 6. 𝒇 𝒙 = 𝟐𝒙 − 𝟐
3. 𝒇 𝒙 = 𝟑𝒙𝟐 + 𝟐𝒙 + 𝟏 7. 𝒇 𝒙 = 𝟑𝒙𝟐 + 𝟒𝒙 + 𝟏
4. 𝒇 𝒙 = 𝟗𝒙𝟐 − 𝟑 8. 𝒇 𝒙 = 𝟒𝒙𝟑 + 𝟗𝒙𝟐
Match the functions in Column A with their
EXERCISE
BY PAIR
corresponding antiderivatives in Column B.

COLUMN A COLUMN B
B 1. 𝒇 𝒙 = 𝟑𝒙𝟐 + 𝟐𝒙 + 𝟏 A. 𝑭 𝒙 = 𝟑𝒙𝟑 − 𝒙 + 𝑪
A 2. 𝒇 𝒙 = 𝟗𝒙𝟐 − 𝟏 B. 𝑭 𝒙 = 𝒙𝟑 + 𝒙𝟐 + 𝒙 + 𝑪
C 3. 𝒇 𝒙 = 𝒙(𝒙 − 𝟒) 𝒙𝟑
C. 𝑭 𝒙 = − 𝟐𝒙𝟐 − 𝟐
𝟑
E 4. 𝒇 𝒙 = 𝒙 + 𝟏 𝒙 − 𝟏
D. 𝑭 𝒙 = 𝑪 − 𝒙𝟑
D 5. 𝒇 𝒙 = −𝟑𝒙𝟐
𝒙𝟑
E. 𝑭 𝒙 = 𝟑
−𝒙+𝟏
Match the functions in Column A with their
QUIZ corresponding antiderivatives in Column B.
COLUMN A COLUMN B
B 1. 𝒇 𝒙 = 𝟔𝒙𝟐 + 𝟒𝒙 + 𝟑 A. 𝑭 𝒙 = −𝟓𝒙𝟑 + 𝒙 + 𝑪
A 2. 𝒇 𝒙 = −𝟏𝟓𝒙𝟐 + 𝟏 B. 𝑭 𝒙 = 𝟐𝒙𝟑 + 𝟐𝒙𝟐 +𝑪
C 3. 𝒇 𝒙 = 𝒙(𝟔𝒙 + 𝟐) C. 𝑭 𝒙 = 𝟐𝒙𝟑 + 𝒙𝟐 −𝟐
𝟏
E 4. 𝒇 𝒙 = 𝒙 + 𝟏 𝟑𝒙 − 𝟏 D. 𝑭 𝒙 = 𝑪 + 𝟐 𝒙𝟔

D 5. 𝒇 𝒙 = 𝟑𝒙𝟓 E. 𝑭 𝒙 = 𝒙𝟑 + 𝒙𝟐 −𝒙 + 𝟏
−𝟑 𝟐
G 6. 𝒇 𝒙 =𝟓 F. 𝑭 𝒙 =
𝟐
𝒙 − 𝒙 + 𝟏𝟎
F 7. 𝒇 𝒙 = −𝟑𝒙 − 𝟏 G. 𝑭 𝒙 = 𝟓(𝒙 + 𝑪)